Effect of Introduction of Neuronal Pathway-Induced Bone Marrow Stromal Cells on Recovery of Movement Impairments and Dopamine Level in Brain Structure of Rats with Parkinson-Like Syndrome - Pyatikop, V. A. (Problems of Cryobiology and Cryomedicine, 2009)
Modelling of Parkinson-like syndrome is achieved by bilateral destruction of substantia nigra manifested as movement disorders and sharp drop of dopamine level in caudate nucleus and frontal cortex of experimental animals. Stereotaxic injection of bone marrow stromal cells induced by neuronal way results in the recoverry of movements in experimental animals. DopaminÐµ level in host animals was not changed.